Anti-genotoxicity and anti-mutagenicity of Apis mellifera venom - Hoshina, Marcia Miyuki [UNESP]; Mann-Morales, Maria Aparecida [UNESP] (Elsevier B.V., 2014)
The search for substances able to inhibit and/or diminish the effects of genotoxic and mutagenic substances has been the target of several investigations performed in recent times. Hymenoptera venoms constitute a considerable source of substances with pharmacological potential. The present study aimed to evaluate the cytotoxic, genotoxic and anti-genotoxic, mutagenic and anti-mutagenic potentials of Apis mellifera venom in HepG2 cells. In this evaluation, the MTT test was applied to determine the most appropriate concentrations for the genotoxicity and mutagenicity tests. It was verified that the concentrations of 0.1, 0.05 and 0.01 mu g/mL were not cytotoxic, hence these concentrations were used in the experiments. For the evaluation of the genotoxic and mutagenic potential of the bee venom the comet assay and the micronucleus test were applied, respectively. The concentrations mentioned above presented both genotoxic and mutagenic potential for HepG2 cells and it was necessary to test lower concentrations of the venom (10 pg/mL, 1 pg/mL and 0.1 pg/mL) for the anti-genotoxicity and anti-mutagenicity tests, which were performed subjecting the cells to the action of MMS (methyl methanesulfonate) in order to verify the ability of the venom to inhibit or diminish the action of this compound, which has a recognized action on the genetic material. Pre-, post-treatment and simultaneous treatment with and without incubation with the venom were performed. It was observed that the lowest three concentrations tested did not present any anti-genotoxic and anti-mutagenic activity on the cells. The use of bee venom for pharmacological purposes in treatments such as cancer must be done with extreme caution, since it was observed that even at very low concentrations the venom can induce genotoxicity and mutagenicity in human cells, as was verified for the HepG2 cells. (C) 2014 Published by Elsevier B.V.
Keywords: MTT assay; Comet assay; Micronucleus; HepG2 cells; Melittin; Bee venom